A comparative study of the semen and seminal characteristics of two breeds of goats (Zambia) - Igboeli, G. (1974)
From a group of mature males goats of Boer and native Zambian goats, eight goats from each breed were selected and semen obtained by means of an electro-ejaculator. Two ejaculates were obtained each week at 24-hour intervals, for a total of six weeks. Ejaculate colours were strikingly variable between goats both within and among breeds, and also within ejaculates of the same goats collected on different days. Semen colour ranged from creamy-white to bright yellow. Boer goats yielded ejaculate volumes twice as large as those of native goats, although sperm motility were not different (P>0.5) between breeds, weeks or ejaculates. Approximately 65 per cent of all spermatozoa in the ejaculates of both breeds were of normal morphology and about 87 per cent were live. Sperm concentration was higher (p